Description of Farmers' Knowledge and Attitudes in Using Pesticides in Koto Tuo Kenagarian IV Village Koto Hilie Kec. Stem Cotton Regency. South Coast. - Armein Lusi Zeswita; Agus Teguh Prihartono; Nurlela Sitepu (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
Pesticides are biocides, which means they are toxic to plants, animals and humans. Inappropriate use of pesticides can result in serious short-term or long-term health problems. The research was conducted with an initial survey in February 2022 in Koto Tuo Village, Nagari IV Koto Hilie. From the results of surveys and interviews with 10 people, it was found that there are still many farmers who have not implemented the behavior of using pesticides in accordance with applicable standards and regulations. The research design is quantitative descriptive, the population in this study is 320 people, the samples taken are 178 farmers. The results of this study found that the farmer's experience determines whether or not the knowledge and attitude of a farmer determines personal and environmental safety. to use pesticides